The influence of recovery management on arm muscle strength in the basketball team of SMA negeri 8 Malang - Gusti Rafi Pangestu; Prisca Widiawati; Muhammad Putra Ramadhan (Physical Education Departement of University PGRI Jombang, 2025)
This study aims to determine the influence of recovery management on the arm muscle strength of the basketball team of SMA Negeri 8 Malang. Using an experimental